2022
DOI: 10.21776/ub.jiip.2022.032.01.11
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Frozen Semen with Different Thawing Duration and Temperature on Simmental Bull

Abstract: This study aimed to determine the accuracy of various thawing duration and temperatures to the quality of Simmental bull frozen semen. The experimental design used was a randomized group design with five treatments and ten replications, then analyzed using Chi-Square to compare the expected percentage of motility is 40%, and total motile spermatozoa are 10 million/straw value of SNI. A further test is carried out with Duncan's Multiple Range Test (DMRT) if there is a difference. The thawing treatments were 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to Salih et al (2021) thawing semen at a temperature of 60 °C in 5 seconds could be an efficient strategy to maintain the quality of semen chicken that is cryopreserved. In mammal species, Zenteno et al (2023) found that the motility of bovine spermatozoa was found to be higher at a thawing temperature of 38 °C for 30 seconds compared to 36 °C for 30 seconds, while Nisa et al (2022) found the best treatment for thawing bovine sperms to be 28 °C during 45 seconds.…”
Section: Advances In Animal Andmentioning
confidence: 99%
“…According to Salih et al (2021) thawing semen at a temperature of 60 °C in 5 seconds could be an efficient strategy to maintain the quality of semen chicken that is cryopreserved. In mammal species, Zenteno et al (2023) found that the motility of bovine spermatozoa was found to be higher at a thawing temperature of 38 °C for 30 seconds compared to 36 °C for 30 seconds, while Nisa et al (2022) found the best treatment for thawing bovine sperms to be 28 °C during 45 seconds.…”
Section: Advances In Animal Andmentioning
confidence: 99%
“…Evaluation of the success of pregnant cattle can be seen from the appearance of signs of estrus at a certain period, the NRR value is used to measure the ability of the cow, when the cow does not show signs of estrus in the estrous cycle, then the acceptor is assumed to be pregnant [8]. Other factors include the ability of the inseminator to thaw [9], the ability of the farmer to recognize signs of estrus, and other external factors that affect the outcome of artificial insemination [10]. According to Susilawati [11], NRR observations can be observed on days 0-30 and 30-60 after AI, while in this study, NRR observations were observed on days 19-22 for NRR1 and days 39-43 for NNR2.…”
Section: Agementioning
confidence: 99%